Liquidación del reajuste de precios, obra readecuación en los sectores Bella María y Nueva Esperanza, Santa Rosa, El Oro - Quinche Rivera, Walter Eduardo (My University, 2023)
The following document includes the study, the liquidation of the price readjustment of a road, plumbing and electrical reading work, on the road to Bella María and the sector. New hope of the City of Santa Rosa, Province of El Oro. The methodology used in this work, in the first instance, was the search for the process in the public procurement portal, with the intention of obtaining the necessary information for the preparation of this project (Budget, APUS, Contract, Schedules). That allow us to carry out the analysis and calculation of the standard crew, polynomial formula, price readjustment and liquidation. To develop this practical work, the bibliography and legal bases provided by the Organic Law of the National Public Procurement System regarding price readjustment and settlement were compiled. In addition, documents published by the State Comptroller General were used, where the minimum wages for labor were established. And finally we will base ourselves on files provided by the INEC, where the construction price indices will be guaranteed. Verifying that said information corresponds to the dates necessary for this work. The liquidation by readjustment of prices obtained in this work, is favorable for the contractor, which justifies the importance of applying this system in civil works. In addition, this value differs from what is published on the public procurement portal, so the causes of said variation were identified in this project.
El siguiente documento comprende el estudio la liquidación del reajuste de precios una obra de readecuación vial, hidrosanitaria y eléctrica, en la vía a Bella María y el sector. Nueva esperanza de la Ciudad de Santa Rosa, Provincia de El Oro. La metodología empleada en este trabajo, en primera instancia fue la búsqueda del proceso en el portal de compras públicas, con la intención de obtener la información necesaria para la elaboración de este proyecto (Presupuesto, APUS, Contrato, Planillas). Que nos permitan realizar el análisis y cálculo de la cuadrilla tipo, fórmula polinómica, reajuste de precios y liquidación. Para desarrollar este trabajo práctico, se recopiló la bibliografía y bases legales que provee la Ley Orgánica del Sistema Nacional de Contratación Pública en cuanto al reajuste de precios y liquidación. Además, se recurrió a documentos publicados por la Contraloría General del Estado en donde se establecen los salarios mínimos de mano de obra. Y por último nos basaremos en archivos proporcionados por el INEC, en donde se establecen los índices de precios de la construcción. Verificando que dicha información corresponda a las fechas necesarias para este trabajo. La liquidación por reajuste de precios obtenida en este trabajo, resulta favorable para el contratista, lo que justifica la importancia de aplicar este sistema en obras civiles. Además, este valor difiere con lo publicado en el portal de compras públicas, por lo que en este proyecto se identificaron las causas de dicha variación.
Keywords: LIQUIDACION; REAJUSTE PRECIO; CUADRILLA TIPO; FORMULA POLINOMICA